2010
DOI: 10.1515/jpem.2010.076
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Growth Consequences of Central Hypothyroidism in Pediatric Patients Receiving Recombinant Human Growth Hormone

Abstract: Objective: Although recombinant human growth hormone (rhGH) can unmask central hypothyroidism, few studies have investigated prevalence, predictors and growth consequences of evolving hypothyroidism in children receiving rhGH based on therapeutic indication. We hypothesized that children with GH deficiency (GHD) and greatest severity of GHD would be most likely to develop central hypothyroidism and decreased growth velocity (GV). Design: Retrospective chart review Patients: Children currently receiving rhGH wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…To our knowledge, this is the first study exploring predictive factors for hypothyroidism during rhGH therapy in a subset of children with isolated idiopathic GHD. Unadjusted comparison of patients who were treated with LT4 with those who were not, showed a slightly lower rhGH dose in the first group, which might be in line with the hypothesis that best responders to rhGH are also more prone to thyroid hormone variations; this is also in agreement with Wong et al [ 25 ], who evaluated patients with multiple GHD etiologies and reported lower doses of rhGH in patients who developed hypothyroidism.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…To our knowledge, this is the first study exploring predictive factors for hypothyroidism during rhGH therapy in a subset of children with isolated idiopathic GHD. Unadjusted comparison of patients who were treated with LT4 with those who were not, showed a slightly lower rhGH dose in the first group, which might be in line with the hypothesis that best responders to rhGH are also more prone to thyroid hormone variations; this is also in agreement with Wong et al [ 25 ], who evaluated patients with multiple GHD etiologies and reported lower doses of rhGH in patients who developed hypothyroidism.…”
Section: Discussionsupporting
confidence: 88%
“…Although the timing of hypothyroidism did not associate with somatropin doses, relevant thyroid function changes were associated with a better response to treatment. Other authors previously reported the need for LT4 during rhGH therapy [6,[15][16][17][18], that occurred earlier in the course of treatment [25], but only two studies directly evaluated patients with isolated idiopathic GHD [15,18]. Researchers suggest that clinically relevant hypothyroidism mostly arises in patients with MPHD, organic lesions on MRI or genetic defects causing GHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline characteristics of the 122 adults with PWS participating in the study are shown in Table 1. The median age was 29 years (IQR 21-39), and the median BMI was 29 kg/m 2 (IQR [26][27][28][29][30][31][32][33][34][35][36]. We included 58 males and 64 females.…”
Section: Baselinementioning
confidence: 99%